2007
DOI: 10.1111/j.1472-765x.2006.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of rhizobia associated with Desmodium species grown in China

Abstract: Aims:  Desmodia are leguminous plants used as important forage and herbal medicine in China. Little information is available about the nodule bacteria of Desmodium species. To understand the genetic diversity of rhizobia associated with Desmodium species grown in China, isolates from temperate and subtropical regions were obtained and analysed. Methods and Results:  A total of 39 rhizobial strains isolated from 9 Desmodium species grown in China were characterized by PCR‐based 16S rDNA gene and 16S–23S rDNA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
1
21
0
1
Order By: Relevance
“…strain. Intriguingly, the L. tenuis symbionts were closely related to rhizobial species that have been shown to be common symbionts of Phaseolus vulgaris (25,40). Unfortunately, despite various attempts we were unable to amplify nodC or nifH gene sequences from Rhizobium symbionts of L. tenuis, which prevented us from obtaining further insight into the origin of their symbiotic capacities.…”
Section: Discussionmentioning
confidence: 91%
“…strain. Intriguingly, the L. tenuis symbionts were closely related to rhizobial species that have been shown to be common symbionts of Phaseolus vulgaris (25,40). Unfortunately, despite various attempts we were unable to amplify nodC or nifH gene sequences from Rhizobium symbionts of L. tenuis, which prevented us from obtaining further insight into the origin of their symbiotic capacities.…”
Section: Discussionmentioning
confidence: 91%
“…Since then, several studies have reported nodulation of various legumes by B. yuanmingense-related rhizobia (8,15,17,30). Studies of host specificity showed that these B. yuanmingense isolates were not capable of effective nodulation of soybean plants (8,17,31,33). Two representative B. yuanmingense soybean isolates were evaluated on soybean plants and were effective in symbiotic N 2 fixation (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Throughout the years, scientists around the world have isolated a great number of bradyrhizobial strains from different climatic and geographical regions from a broad spectrum of host plants, such as Glycine max, 3) Parasponia, 4) Arachis hypogaea, 5) Lupinus, 6) Aeschynomene, 7) Beta vulgaris, 8) Adenocarpus, Chamaecytisus, Spartocytisus, 9) and Desmodium. 10) Diversity studies have been conducted to gain a better understanding of the taxonomy and distribution of bradyrhizobia, and to screen for strains that might be of use in agriculture and environmental management. An abundance of attention was directed towards the selection, identification, and development of new strains of bradyrhizobia with novel and useful characteristics.…”
mentioning
confidence: 99%